Pemahaman Bahaya Narkoba Dikalangan Pelajar Madrasah Aliyah Negeri 1 Medan - Arlina; Khairi, Mhd Hazrat; Aqilla, Najla Puteri; Rambe, Rosnaini Br (At-Tadris: Journal of Islamic Education, 2023)
The rampant drug abuse among students has received serious attention from all parties because it damages the future generations of the nation. Drugs are substances or drugs that can cause the effects of loss of consciousness, hallucinations, and excitatory power. Understanding the dangers of narcotics is very important among today's students, considering that they are the next generation of the nation in the future. This study aims to find out how the understanding of MAN 1 MEDAN students, regarding the dangers of narcotics. The research methods used are quantitative descriptive methods using data collection techniques, compiling and interpreting them. The result of this study is the Understanding of the Dangers of Drugs Among Students of Madrasah Aliyah Negeri 1 Medan is that students have a fairly good level of understanding, which is around 62.5% about understanding the dangers of drugs.